PLX4032 resistance of patient-derived melanoma cells: crucial role of oxidative metabolism - Garbarino, Ombretta; Valenti, Giulia Elda; Monteleone, Lorenzo; Pietra, Gabriella; Mingari, Maria Cristina; Benzi, Andrea; Bruzzone, Santina; Ravera, Silvia; Leardi, Riccardo; Farinini, Emanuele; Vernazza, Stefania; Grottoli, Melania; et al. (Frontiers in Oncology, 2023)
Background: Malignant melanoma is the most lethal form of skin cancer which shows BRAF mutation in 50% of patients. In this context, the identification of BRAFV600E mutation led to the development of specific inhibitors like PLX4032. Nevertheless, although its initial success, its clinical efficacy is reduced after six-months of therapy leading to cancer relapse due to the onset of drug resistance. Therefore, investigating the mechanisms underlying PLX4032 resistance is fundamental to improve therapy efficacy. In this context, several models of PLX4032 resistance have been developed, but the discrepancy between in vitro and in vivo results often limits their clinical translation. Methods: The herein reported model has been realized by treating with PLX4032, for six months, patient-derived BRAF-mutated melanoma cells in order to obtain a reliable model of acquired PLX4032 resistance that could be predictive of patient’s treatment responses. Metabolic analyses were performed by evaluating glucose consumption, ATP synthesis, oxygen consumption rate, P/O ratio, ATP/AMP ratio, lactate release, lactate dehydrogenase activity, NAD+/NADH ratio and pyruvate dehydrogenase activity in parental and drug resistant melanoma cells. The intracellular oxidative state was analyzed in terms of reactive oxygen species production, glutathione levels and NADPH/NADP+ ratio. In addition, a principal component analysis was conducted in order to identify the variables responsible for the acquisition of targeted therapy resistance. Results: Collectively, our results demonstrate, for the first time in patient-derived melanoma cells, that the rewiring of oxidative phosphorylation and the maintenance of pyruvate dehydrogenase activity and of high glutathione levels contribute to trigger the onset of PLX4032 resistance. Conclusion: Therefore, it is possible to hypothesize that inhibitors of glutathione biosynthesis and/or pyruvate dehydrogenase activity could be used in combination with PLX4032 to overcome drug resistance of BRAF-mutated melanoma patients. However, the identification of new adjuvant targets related to drug-induced metabolic reprogramming could be crucial to counteract the failure of targeted therapy in metastatic melanoma.